2020
DOI: 10.1021/acsanm.0c02048
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Nanosensor-Based Virus and Pathogen Detection Strategies before and during COVID-19

Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), is a threat to the global healthcare system and economic security. As of July 2020, no specific drugs or vaccines are yet available for COVID-19; a fast and accurate diagnosis for SARS-CoV-2 is essential in slowing the spread of COVID-19 and for efficient implementation of control and containment strategies. Magnetic nanosensing is an emerging topic representing the frontiers of current bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 168 publications
0
72
0
Order By: Relevance
“…The prominent magnetic and more specifically superparamagnetic properties along with the intense signal due to the slight background noise in biological specimens makes MNPs interesting materials for biosensing. 121 In magnetic nanosensors, MNPs could be decorated with antibodies or oligonucleotide probes (RNA/DNA sequences) special to the target analytes. As mentioned before, PCR-based techniques are the gold standard diagnosis methods to detect infected patients.…”
Section: Diagnostics For Coronavirusesmentioning
confidence: 99%
“…The prominent magnetic and more specifically superparamagnetic properties along with the intense signal due to the slight background noise in biological specimens makes MNPs interesting materials for biosensing. 121 In magnetic nanosensors, MNPs could be decorated with antibodies or oligonucleotide probes (RNA/DNA sequences) special to the target analytes. As mentioned before, PCR-based techniques are the gold standard diagnosis methods to detect infected patients.…”
Section: Diagnostics For Coronavirusesmentioning
confidence: 99%
“…Among the others, bio-sensing technologies, magnetoresistive biosensors, electrochemical biosensors, and plas monic biosensors have attracted attention in the last years. Wu et al (2020) proposed an analysis of magnetic nano-sensors for virus and pathogen detection before . They demonstrated that magnetic nano-sensors are more versatile and applicable for antibody, antigen, and nucleic acid detection.…”
Section: State Of the Art On Sensors And Technologies For Detecting Pmentioning
confidence: 99%
“…Wu et al presented a portable GMR bio-detector, called Z-Lab, able to detect the Influenza-A Virus (IAV). This bio-detector reached a Limit of Detection (LOD) of 15 ng/mL for the H1N1 virus, and a 125 TCID50/mL LOD for the purified H3N2 variant virus (H3N2v), with an overall assay time lower than 10 min ( Figure 2) (Wu et al, 2017(Wu et al, , 2020. The electronic section includes a microcontroller, a 24-bit codec, a Wheatstone Bridge for adjusting the offset on the carrier signal, a coil driver, and a USB and Bluetooth communication section.…”
Section: State Of the Art On Sensors And Technologies For Detecting Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Various platforms have been proposed for detection of SARS-CoV-2-related genetic material or viral load and for protein/antibody sensing 23-25 26 , including nanophotonics 27 , magnetic 28 and electrochemical 29 sensors. Among them, surface plasmon resonance (SPR) sensing is a label-free sensing technique 30 that is particularly sensitive for large biomolecules such as antibodies.…”
Section: Introductionmentioning
confidence: 99%